PEMBANGUNAN IRIGASI WIDAS DAN PENGARUHNYA TERHADAP EKONOMI DAN LINGKUNGAN DI NGANJUK, JAWA TIMUR 1978-2010 - Ardhian Dwi Prabowo; S Nawiyanto (Handep: Jurnal Sejarah dan Budaya, 2020)
The paper discusses Widas irrigation development and effects on the socio-economy andenvironment of people of Nganjuk Regency in 1978-2010. The research examines theconditional factors promoting Widas irrigation development, the development process andeffects on the local economy and environment. The study used the historical methodconceptualized by Kuntowijoyo which included topic selction, source collection, verification,interpretation, and historiography. Widas river has offered important benefits for thecommunity’s economy, especially the agricultural sector; however, it still causes floodswhich leads to a big loss to Nganjuk people. The irrigation development was a programdesigned to bring multiple benefits, particularly to control the severe flood of Widas riverand to promote agricultural production in Nganjuk area. It successfully increasesagricultural production and improves the community’s economy by opening opportunitiesto change cropping patterns and freshwater fish farming. However, this project has notbeen able to free Nganjuk community from flooding because the forest damage in theupstream area of Widas river disrupts the hydrological system.